Efficacy of Intermittent, Oral Famciclovir Prophylaxis for Bortezomib-Induced Herpes Zoster in Multiple Myeloma Patients - Zheng, Gaofeng; Guan, Fangshu; Han, Xiaoyan; Yang, Li; Zhao, Yi; Yang, Yang; Zhang, Enfang; He, Jingsong; He, Donghua; Wu, Wenjun; Huang, He; Cai, Zhen (Frontiers in Oncology, 2022)
Objective To explore the efficacy and safety of intermittent, oral famciclovir prophylaxis for bortezomib-induced herpes zoster in multiple myeloma patients. Method We retrospectively analyzed the incidence of bortezomib treatment-related varicella-zoster virus reactivation in 719 newly-diagnosed multiple myeloma patients receiving intermittent oral famciclovir prophylaxis, continuous oral acyclovir prophylaxis or no prophylaxis. The definition of intermittent oral famciclovir prophylaxis was oral famciclovir at a dose of 250mg twice daily for 9 days after finishing the last dose of bortezomib therapy every cycle. Age, gender, stage per the International Staging System, type of M protein, baseline of absolute lymphocyte count, absolute neutrophil count, and absolute monocyte count were analyzed to find the potential factors that could predispose to herpes zoster infections. Results Varicella-zoster virus infection occurred in 96 patients (13.4%) during bortezomib treatment. The incidence of herpes zoster was significantly higher in the non-prophylaxis group compared with the prophylaxis group (22.9% vs 8.2% P<0.001), while the rate was similar between the intermittent oral famciclovir group and the continuous oral acyclovir group (8.4% vs 7.9% P=0.835). Hepatic and renal toxicity were observed in 12% and 2.8% of the patient respectively in the intermittent famciclovir group, which was similar in the continuous acyclovir group (18.1% and 4.2%). The prophylactic use of antiviral agents is a predictive factor for varicella-zoster virus reactivation. Conclusion Intermittent famciclovir prophylaxis is effective and safe in preventing herpes zoster development and can markedly reduce the duration of oral medicine treatment compared with continuous acyclovir prophylaxis.